Karakteristik dan Faktor Motivasi Calon Mahasiswa dalam Memilih Program Studi Pendidikan Agama Islam - Efsa Wijaya; Bramana Nanditya Putra; Rafi Bagus Adi Wijaya (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to understand the demographic characteristics and motivational factors of prospective students in choosing the Islamic Religious Education (PAI) Study Program at Universitas Islam Nusantara Al-Azhaar Lubuklinggau. The background of this research is based on the high interest of prospective students in PAI at various Islamic higher education institutions, which is largely driven by religious motivation and career orientation. This study employed a quantitative approach with a descriptive cross-sectional design. The research instrument was an online questionnaire covering demographic data, sources of information, decision-influencing factors, and 30 motivation statement items measured using a Likert scale. The respondents consisted of 35 prospective new PAI students for the 2025/2026 academic year. The results indicate that religious motivation, such as the desire to deepen religious knowledge, strengthen faith, and become a religious individual constitutes the dominant factor. Career-related factors, particularly aspirations to become religious teachers and educators in Islamic institutions, also play a significant role. Comparative analysis between students with religious and general educational backgrounds revealed no significant differences, although there was a tendency for variation in external and intrinsic factors. These findings confirm that the motivation of prospective PAI students is multidimensional, with religiosity as the dominant aspect, and contribute to the development of Islamic values-based academic and career guidance and counseling services in higher education.